Two distinct conformational states define the interaction of human RAD51‐ATP with single‐stranded DNA. (5th March 2018) - Brouwer, Ineke; Moschetti, Tommaso; Candelli, Andrea; Garcin, Edwige B; Modesti, Mauro; Pellegrini, Luca; Wuite, Gijs JL; Peterman, Erwin JG
Abstract: An essential mechanism for repairing DNA double‐strand breaks is homologous recombination (HR). One of its core catalysts is human RAD51 (hRAD51), which assembles as a helical nucleoprotein filament on single‐stranded DNA, promoting DNA‐strand exchange. Here, we study the interaction of hRAD51 with single‐stranded DNA using a single‐molecule approach. We show that ATP‐bound hRAD51 filaments can exist in two different states with different contour lengths and with a free‐energy difference of 4 kB T per hRAD51 monomer. Upon ATP hydrolysis, the filaments convert into a disassembly‐competent ADP‐bound configuration. In agreement with the single‐molecule analysis, we demonstrate the presence of two distinct protomer interfaces in the crystal structure of a hRAD51‐ATP filament, providing a structural basis for the two conformational states of the filament. Together, our findings provide evidence that hRAD51‐ATP filaments can exist in two interconvertible conformational states, which might be functionally relevant for DNA homology recognition and strand exchange. Synopsis: Single‐molecule studies of RAD51 binding to single‐stranded DNA, together with a new crystal structure of the hRAD51 filament, reveal two distinct conformational states of ATP‐bound RAD51 that may be important for DNA homology recognition and strand exchange. ATP‐bound hRAD51‐ssDNA filaments exist in two distinct states with different contour lengths and with a free energy difference of ˜4 kBT per hRAD51 monomer. hRAD51 disassembly from ssDNA is independent of tension in the DNA template and occurs from an ADP‐bound state. The crystal structure of a hRAD51‐ATP filament reveals the presence of two distinct protomer interfaces. Combined evidence from single‐molecule and crystallographic experiments shows that the ATP‐bound hRAD51‐ssDNA filament is a highly flexible entity. Abstract : Single‐molecule studies of RAD51 DNA binding and a new crystal structure of the hRAD51 filament suggest that different conformations of ATP‐bound RAD51 may be involved in DNA homology recognition and strand exchange.